Climate-smart food systems: integrating adaptation and mitigation strategies for sustainable agriculture in South Africa - Rudzani V. A. Mudzielwana (Frontiers in Sustainable Food Systems)
AimClimate change presents significant challenges to food security, particularly in vulnerable regions like South Africa. This review examines climate-smart food systems (CSFS) as an integrated approach to enhancing agricultural resilience, mitigating greenhouse gas emissions, and ensuring sustainable food production.IntroductionThe agricultural sector must simultaneously adapt to shifting climatic conditions and reduce its environmental impact.MethodsThis study synthesizes current literature on adaptation strategies, such as drought-resistant crops, precision agriculture, and agroecological practices, alongside mitigation efforts, including carbon sequestration, emissions reductions in livestock, and circular food systems.ResultsFindings highlight key barriers to CSFS implementation, including financial constraints, inadequate technical support, and fragmented policies. Policy interventions, multi-stakeholder collaborations, and emerging technologies are crucial in overcoming these challenges.DiscussionStrengthening governance, financial mechanisms, and knowledge-sharing platforms is essential for the widespread adoption of climate-smart strategies.ConclusionBy aligning adaptation, mitigation, and policy efforts, South Africa can foster a resilient agricultural sector that supports food security and sustainable development in the face of climate change.